Ubisol-Q10, a Nanomicellar and Water-Dispersible Formulation of Coenzyme-Q10 as a Potential Treatment for Alzheimer's and Parkinson's Disease - Darcy Wear; Caleb Vegh; Jagdeep K. Sandhu; Marianna Sikorska; Jerome Cohen; Siyaram Pandey (MDPI AG, 2021)
The world continues a desperate search for therapies that could bring hope and relief to millions suffering from progressive neurodegenerative diseases such as Alzheimer's (AD) and Parkinson's (PD). With oxidative stress thought to be a core stressor, interests have long been focused on applying redox therapies including coenzyme-Q10. Therapeutic use has failed to show efficacy in human clinical trials due to poor bioavailability of this lipophilic compound. A nanomicellar, water-dispersible formulation of coenzyme-Q10, Ubisol-Q10, has been developed by combining coenzyme-Q10 with an amphiphilic, self-emulsifying molecule of polyoxyethanyl α-tocopheryl sebacate (derivatized vitamin E). This discovery made possible, for the first time, a proper assessment of the true therapeutic value of coenzyme-Q10. Micromolar concentrations of Ubisol-Q10 show unprecedented neuroprotection against neurotoxin exposure in in vitro and in vivo models of neurodegeneration and was extremely effective when delivered either prior to, at the time of, and most significantly, post-neurotoxin exposure. These findings indicate a possible way forward for clinical development due to effective doses well within Federal Drug Administration guidelines. Ubisol-Q10 is a potent mobilizer of astroglia, antioxidant, senescence preventer, autophagy activator, anti-inflammatory, and mitochondrial stabilizer. Here we summarize the work with oil-soluble coenzyme-Q10, its limitations, and focus mainly on efficacy of water-soluble coenzyme-Q10 in neurodegeneration.